2019
DOI: 10.1186/s12934-019-1077-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of l-alanyl-l-glutamine by immobilized Pichia pastoris GS115 expressing α-amino acid ester acyltransferase

Abstract: Backgroundl-Alanyl-l-glutamine (Ala-Gln) represents the great application potential in clinic due to the unique physicochemical properties. A new approach was developed to synthesize Ala-Gln by recombinant Escherichia coli OPA, which could overcome the disadvantages of traditional chemical synthesis. Although satisfactory results had been obtained with recombinant E. coli OPA, endotoxin and the use of multiple antibiotics along with toxic inducer brought the potential biosafety hazard for the clinical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In K. phaffii and S. cerevisiae, it was previously observed that expressed SsAet was secreted with lower activity; thus, we inferred that glycosylation occurred and decreased the activity. 21 Considering the tolerance and robustness of K. phaffii with a relatively low glycosylation level, we selected K. phaffii KM71 as the chassis host to investigate the effect of N-linked glycosylation on SsAet, avoiding the interference of other types of glycosylation, such as O-glycosylation and C-glycosylation. The codon-optimized SsAET K gene was expressed with (Aet9), or without (Aet3) an α-factor signal peptide, and then the secreted Aet9 and nonsecreted Aet3 were purified and characterized by SDS-PAGE and western blotting.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In K. phaffii and S. cerevisiae, it was previously observed that expressed SsAet was secreted with lower activity; thus, we inferred that glycosylation occurred and decreased the activity. 21 Considering the tolerance and robustness of K. phaffii with a relatively low glycosylation level, we selected K. phaffii KM71 as the chassis host to investigate the effect of N-linked glycosylation on SsAet, avoiding the interference of other types of glycosylation, such as O-glycosylation and C-glycosylation. The codon-optimized SsAET K gene was expressed with (Aet9), or without (Aet3) an α-factor signal peptide, and then the secreted Aet9 and nonsecreted Aet3 were purified and characterized by SDS-PAGE and western blotting.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Therefore, Komagataella phaffii, which was granted a qualified presumption of safety (QPS) status by European Food Safety Authority (EFSA), and Saccharomyces cerevisiae, which was determined to be generally recognized as safe (GRAS) by the Food and Drug Administration (FDA), were used as safer chassis cells to design new biocatalysts. Unexpectedly, obviously lower molar yields were obtained, which were approximately 70 and 50% of that of OPA in the recombinant Pichia pastoris strain GS115-pPIC9- SsAET p (GPA p ) and the recombinant S. cerevisiae strain with a surface-displayed SsAet (unpublished data).…”
Section: Introductionmentioning
confidence: 97%
“…This is the first time that we can achieve a higher production in the immobilized P. pastoris. In previous experiments, cells were immobilized in a polymeric matrix, and a significant reduction in cell performance and production was inevitable [12,13,15,16].…”
Section: Recombinant Hsa Productionmentioning
confidence: 99%
“…Hence, there is a vast attempt to develop cell immobilization techniques as an efficient alternative for centrifugation. The P. pastoris system is not exceptional and several attempts were done to efficiently immobilize this cell for the production of valuable products, such as HSA, alcohol oxidase, l-alanyl-l-glutamine, and invertase [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cell immobilization techniques such as entrapment in polymers have been extensively used in many applications ranging from wastewater treatment ( 11 , 12 ) to the production of valuable metabolites such as alcohol ( 13 , 14 ), vitamins ( 15 ), antibiotics ( 16 ), and amino acids ( 17 ). The method of cell encapsulation in a matrix can provide an array of beneficial features ( 18 ), the most considerable being that metabolite production and purification processes would become simpler.…”
Section: Introductionmentioning
confidence: 99%